2017
DOI: 10.22555/joeed.v4i1.1001
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Level in Students of Public Speaking: Causes and Remedies

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 0 publications
5
70
0
11
Order By: Relevance
“…Other scholars (e.g. Anandari, 2015;Rahman, 2017;Raja, 2017) have also found that speaking anxiety mostly emerged when they had to speak in public. As a consequence, many students tended to feel uncomfortable, shy, frustrated, helpless, and embarrassed when speaking in front of others.…”
Section: Performance Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Other scholars (e.g. Anandari, 2015;Rahman, 2017;Raja, 2017) have also found that speaking anxiety mostly emerged when they had to speak in public. As a consequence, many students tended to feel uncomfortable, shy, frustrated, helpless, and embarrassed when speaking in front of others.…”
Section: Performance Factorsmentioning
confidence: 94%
“…Students worry too much that the audience will not comprehend their speech. Moreover, Raja (2017) found that the size of the audience also played a major role on students' performance. Audience size has a strong impact on a student's performance and level of nervousness as the student may feel it will be difficult to handle the audience interest, especially when there is a very big audience.…”
Section: Cognitive Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the students to develop their speaking abilities, they have to address first their public speaking anxiety. Students who have this anxiety can perform well in the class if they can find strategies to combat their fears (Raja, 2017). Table 8 shows the responses of the respondents every after the activity.…”
Section: Significant Difference In the Oral Communication Skills Levementioning
confidence: 99%
“…Recommendations to improve science communication are plentiful. Speaking with confidence and reducing apprehension is an oft mentioned initial step, covered across public speaking courses and texts (Pearson, DeWitt, Child, Kahl, & Dandamudi, ; Raja, ). The use of human‐interest stories can be useful for gaining audience attention (Jebril, Vreese, Dalen, & Albæk, ; Valkenburg, Semetko, & De Vreese, ).…”
Section: Making Effective Stem Science Communicatorsmentioning
confidence: 99%